2021
DOI: 10.1136/bmjspcare-2021-003182
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis and peritoneal dialysis—health-related quality of life: systematic review plus meta-analysis

Abstract: BackgroundPatients with end-stage renal disease undergoing haemodialysis experience a variety of stressors leading to decreased level of quality of life (QoL). Thus, in this study, we aimed to review the current literature and identify factors affecting the health-related QoL (HRQoL) in these patients.MethodsA total of 147 studies were extracted from databases of Web of Science, PubMed, Scopus, Google Scholar, and Embase published between January 2000 and December 2020. Data were analysed using R software and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
0
13
0
3
Order By: Relevance
“…For instance, the SONG-PD group found that 76% of studies reported both dimensions; an additional 14% and 10% of studies reported obligatory and non-obligatory dimensions, respectively 24 . Patients receiving PD often have a better employment status than those treated with HD 106 110 , probably because they need to spend less time in a treatment facility. One study reported that PD was associated with a 4% increased probability of employment, 6% reduced probability of disability pension requirement and increased work income compared with HD 111 .…”
Section: Global Patient-reported Pd Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the SONG-PD group found that 76% of studies reported both dimensions; an additional 14% and 10% of studies reported obligatory and non-obligatory dimensions, respectively 24 . Patients receiving PD often have a better employment status than those treated with HD 106 110 , probably because they need to spend less time in a treatment facility. One study reported that PD was associated with a 4% increased probability of employment, 6% reduced probability of disability pension requirement and increased work income compared with HD 111 .…”
Section: Global Patient-reported Pd Outcomesmentioning
confidence: 99%
“…The ChinaQ study randomly assigned 725 patients across China to PD or HD and found that the burden of kidney disease on the PD group was non-inferior to that of the HD group 112 . However, studies comparing QOL between patients receiving HD or PD have tended to show better QOL in PD than in HD 108 110 . This difference might result from greater lifestyle flexibility, better ability to perform exchanges at home (or in a comfortable place that imposes less restriction), and better dietary flexibility in patients receiving PD 110 .…”
Section: Global Patient-reported Pd Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis involving 147 studies reported a pooling mean HRQOL score for patients undergoing dialysis as 64.25 [95% confidence interval (CI): 55.67–72.82] ( Raoofi et al, 2021 ). In the present study, the overall mean score of HRQOL was modestly lower than the results mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to ICHD, PD gives the opportunity to dialyze at home, independently or with the help of a caregiver. Additionally, the short amount of time required for fluid exchange allows a flexible schedule and the opportunity to work, travel or participate in recreational activities [179][180][181]. Using the KDQOL SF 1.3, Wakeel et al compared the QoL of 200 patients on ICHD or PD in Saudi Arabia.…”
Section: Quality Of Life On the Transplant Waiting Listmentioning
confidence: 99%